Understanding regular exercise behavior in frail older adults: a structural equation model based on social-cognitive variables - Shiqi Yu; Jie Lin; Siping Song; Shuqi Huang; Fan Liu; Mingzhao Xiao (BMC Geriatrics)
Abstract Background Regularly engaging in exercise has been recognized as the only therapy found to consistently manage frailty. This study applies structural equation modeling (SEM) to integrate the theoretical perspective of Social cognitive theory (SCT) to better understand and promote regular exercise behavior among frail older adults, providing a foundation for enhancing exercise engagement in this vulnerable population. Methods A total of 306 frail older adults in Chengdu, China, were selected in this cross-sectional study. Participants completed the the FRAIL scale, the Self-Efficacy for Exercise (SEE) Scale, the behavioral regulation in exercise questionnaire (BREQ-2), the Outcome Expectations for Exercise (OEE), the Exercise Social Support (ESS) Scale. Structural equation modeling (SEM) was used to specify hypothesis between components of social-cognitive theory on regular exercise behavior among frail seniors. Results The percentage of regular exercise behavior was 29.1% among participants. There were statistically significant differences in the regular exercise behavior for demographic characters of occupation, disposable monthly income, frail phenotype of fatigue, resistance and weight loss (p < 0.05). SEM showed that the exercise self-efficacy (β = 0.52, p < 0.001) and exercise outcome expectation (β = 0.45, p < 0.011) are the strongest determinants of regular exercise behavior, while social support (β = 0.092, p > 0.05) and self-regulation (β = 0.05, p > 0.05) are non-determinant. Conclusion Our study underscores that adherence to regular and structured exercise regimens remains low among frail older adults, suggesting that this population may not be fully benefiting from scientifically guided exercise programs. Integrating self-efficacy and outcome expectations into further exercise promotion is critical. Patient-centered approach is essential for developing more effective and sustainable exercise interventions.